2018
DOI: 10.1186/s12957-018-1467-6
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction options following pancreaticoduodenectomy after Roux-en-Y gastric bypass: a systematic review

Abstract: BackgroundObesity is a risk factor for pancreatic cancer which may be treated with Roux-en-Y gastric bypass and represents an increasing morbidity. Post-RYGB anatomy poses considerable challenges for reconstruction after pancreaticoduodenectomy (PD), a growing problem encountered by surgeons. We characterize specific strategies used for post-PD reconstruction in the RYGB patient.MethodsPubMed search was performed using MeSH terms “Gastric Bypass” and “Pancreaticoduodenectomy” between 2000 and 2018. Articles re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 59 publications
(71 reference statements)
0
19
0
Order By: Relevance
“…As laparoscopic techniques have progressed, more and more complicated operations are completed by laparoscopy [ 13 , 14 ] with an acceptable complication. Post-operation pancreatic leakage is considered to be the biggest obstacle to PD.…”
Section: Discussionmentioning
confidence: 99%
“…As laparoscopic techniques have progressed, more and more complicated operations are completed by laparoscopy [ 13 , 14 ] with an acceptable complication. Post-operation pancreatic leakage is considered to be the biggest obstacle to PD.…”
Section: Discussionmentioning
confidence: 99%
“…This study was based on 96 patients under 55 different surgeons in 28 centres globally. 4,6,7 Multiple potential options for PD in patients with a previous RYGB have been described in overseas case reports, with the major surgical decisions being the degree of resection/preservation of both the gastric remnant and the biliopancreatic limb. 4 The gross advantages/disadvantages have been described by Mak et…”
Section: Discussionmentioning
confidence: 99%
“…Although this meta-analysis studies the effect of drainage in MOJ, drainage is not necessary for MOJ in some cases. Some scholars theorize that pancreaticoduodenectomy can be performed without cholangitis in the presence of obstructive jaundice (28). All the ten studies included in this study were retrospective cohort studies that were clearly grouped, and no selective results were reported.…”
Section: Discussionmentioning
confidence: 99%